2013
DOI: 10.1111/jpi.12044
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and its potential biological functions in the fruits of sweet cherry

Abstract: Melatonin is a well-known molecule which possesses many beneficial effects on human health. Many agriculture products provide natural melatonin in the diet. Cherry is one such fruit as they are rich in melatonin. In order to understand the biological roles of melatonin in cherry fruit, melatonin synthesis and its changes over 24 hr period were systematically monitored both during their development and in the ripe cherries in two cultivars, 'Hongdeng' (Prunus avium L. cv. Hongdeng) and 'Rainier' (Prunus avium L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
192
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(210 citation statements)
references
References 58 publications
15
192
1
2
Order By: Relevance
“…(Tal et al 2011) and also in higher plants: Chenopodium rubrum L. (Kolar et al 1995(Kolar et al , 1997Wolf et al 2001), Eichhornia crassipes (hyacinth) (Tan et al 2007), Vitis vinifera (Boccalandro et al 2011), and Prunus sp. (Zhao et al 2013), pointing to its possible role as a regulator of light/dark-mediated rhythms. The changes mentioned above were associated with the external factor-photoperiod.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…(Tal et al 2011) and also in higher plants: Chenopodium rubrum L. (Kolar et al 1995(Kolar et al , 1997Wolf et al 2001), Eichhornia crassipes (hyacinth) (Tan et al 2007), Vitis vinifera (Boccalandro et al 2011), and Prunus sp. (Zhao et al 2013), pointing to its possible role as a regulator of light/dark-mediated rhythms. The changes mentioned above were associated with the external factor-photoperiod.…”
Section: Resultsmentioning
confidence: 97%
“…This implies the role of the described indoleamine also in combat against biotic stresses. The importance of melatonin in stress effects/injuries limitation during different developmental stages including flowering, fruiting, and senescence was discussed (Kolar et al 2003;Arnao and Hernández-Ruiz 2009a;Zhao et al 2013;. An increase in melatonin level in sunflower seeds during sprouting was also observed (Cho et al 2008).…”
Section: Introductionmentioning
confidence: 90%
“…Two peaks of melatonin production in plants are not rare and have previously been documented. For example, Zhao et al (2013) reported dual peaks of melatonin production during a 24-h period in cherry fruits grown under natural environment (i.e. plants exposed to daily changing light and temperature conditions).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several studies demonstrated dual melatonin peaks in the circadian cycle of some plants. For example, two peaks of melatonin production, just before sunrise and late in the afternoon when peak temperatures occurred, have been reported in sweet cherry fruits (Zhao et al, 2013) and in apple leaves (Zuo et al, 2014) during a 24-h period. Similar results were also found in the leaves and roots of lupin and barley plants (Arnao and Hernández-Ruiz, 2015a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation